Effect of flaxseed alcoholic extract on naphthalene-induced liver damage in Syrian hamsters (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
The study aimed to examine the effect of the alcoholic extract of the flaxseed on naphthalene-induced hepatotoxicity in the Syrian hamsters and to identify some of the resulted biochemical and histological changes. This study has been conducted on 32 hamster  in the four equal groups. The animals of the first group (control) / the group I / have been immunized with the physiological solution NACL at a concentration of (0.9%). However, the second group / the group II/ have been extracted with the alcoholic extract of the flaxseed only in dose of (30 mg / 100 g) once daily for three weeks. also, the third group/ the group III/  have been dosed with naphthalene (100 mg / 100 g) daily for three weeks, the Group IV have been administered simultaneously with the alcoholic extract of the flaxseed and naphthalene at the same level in terms of the dose and treatment duration. The results of the biochemical study showed a significant increase (P